Extended coupled cluster method for potential energy surface: a decoupled approach - Joshi, Sayali P.; Vaval, Nayana (Chemical Physics Letters, 2014)
Extended coupled cluster (ECC) method has been implemented extensively for the calculation of molecular properties. In this Letter we report the potential energy surface (PES) study using coupled and a decoupled approximation of ECC. HF, N-2 and C-2 are studied as test systems. N-2 and C-2 being doubly and triply bonded, are considered to be interesting systems for PES study. We compare our results with full CI (FCI) results wherever available. Decoupled approach within ECC framework shows good convergence for all the molecules. (C) 2014 Elsevier B.V. All rights reserved.